Modelling the capture of gasoline engine exhaust particulate matter in three-way catalytic converters. (1st January 2014) - Vineeth, Valsan; Samuel, Stephen
The aim of this work was to numerically model the effect of a three-way catalytic converter on nano-scale particulate matter from a gasoline direct injection engine. The work used a deep bed filtration model to simulate and validate experimental findings. A 1.6L, gasoline direct injection, spark ignition, turbocharged and intercooled Euro IV engine was used for experimentation. The capture efficiency was experimentally determined by measuring pre and post-catalyst particulate matter numbers using a DMS-500 differential mobility spectrometer at different dilution ratio settings. Despite variable experimental results at lower engine speeds and loads, the model was capable of predicting catalytic converter particle capture efficiency in the majority of cases. This indicates that deep bed filtration theory can indeed be used to explain nano-scale particle capture within three-way catalytic converters. The results also suggest that there is no significant agglomeration of particles within the catalytic converter. This research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors.